Facile green preparation of single- and two-component modified activated carbon fibers for efficient trace heavy metals removal from drinking water. (March 2023) - Zuo, Qi; Zheng, Hong; Zhang, Pengyi; Zhang, Yu; Zhang, Jiejing; Zhang, Baichao
Abstract: Trace heavy metals exist in drinking water, having great adverse effects on human health and making it a huge challenge to remove. Herein, novel materials have been prepared by a simple and green method using single- (polydopamine (PDA) or 2, 3-dimercaptopropanesulfonic sodium (DMPS)) (PDA-OACF or DMPS-OACF) and two-component (PDA and DMPS) (DMPS-PDA-OACF) functionalized activated carbon fibers pretreated by hydrogen peroxide for the removal of trace heavy metals. The as-prepared DMPS-OACF (7.5, 20) under DMPS addition of 7.5 mg and sonication time of 20 min retained large specific surface area, micro-mesoporous structure and rich functional groups and showed better adsorption performance for trace lead and mercury. It also exhibited wide applicable ranges of pH (3.50–10.50) and concentration (50–1136 μg L −1 ), rapid adsorption kinetics, and excellently selective removal performance for trace lead. The maximum lead adsorption capacity reached 16.03 mg g −1 when the effluent lead concentration met World Health Organization (WHO) standard and the adsorbent can be regenerated by EDTA solution. The fitting results of adsorption kinetics and isotherm models revealed that the lead adsorption process was multi-site adsorption on heterogeneous surfaces and chemical adsorption. The excellent adsorption properties for trace heavy metals were attributed that the sulfur/oxygen/nitrogen-containing functional groups boosted diffusion and adsorption by electrostatic attraction and coordination, suggesting that DMPS-OACF (7.5, 20) has great application potential in the removal of trace heavy metals. Graphical abstract: Image 1 Highlights: Single- and two-component modified ACFs were prepared by a simple and green method. DMPS-OACF (7.5, 20) shows fast adsorption, high selectivity and wide applicable range. DMPS-OACF (7.5, 20) shows high adsorption capacity of 16.03 mg g −1 meeting WHO standard. Rich S/O/N functional groups boost diffusion and adsorption of trace heavy metals. DMPS-OACF (7.5, 20) shows good application prospect for drinking water purification.